Immunosuppression of the Trimellitic Anhydride-Induced Th2 Response by Novel Nonanatural Products Mixture in Mice. (19th November 2013) - Bae, Min-Jung; Shin, Hee Soon; Shon, Dong-Hwa
Abstract : Many natural dietary products prevent or cure allergic inflammation; however, the ability of mixtures of these natural medicinals to suppress allergic skin inflammation is unknown. We examined the inhibitory effects of nonanatural products mixture (NPM-9), which provides immunoregulatory activation, on Th2-mediated skin allergic inflammation. Oral administration of NPM-9 in mice reduced ear thickness and specific IgE production in trimellitic anhydride- (TMA-)induced contact hypersensitivity (CHS). NPM-9 also suppressed IL-4 and IL-1β production in splenocytes but prevented only TMA-induced IL-1β production in inflamed ears. To characterize the mechanism of this effect, we examined NPM-9 immunosuppression on an OVA-induced Th2 allergic state. Oral administration of NPM-9 inhibited Th2-mediated serum IgE overproduction. NPM-9 also downregulated the polarized Th2 response, whereas it upregulated Th1 response in splenocytes. These data suggest that NPM-9 may be a useful therapeutic agent for allergic inflammatory diseases through its suppression of the Th2-mediated allergic response.